1995
DOI: 10.2337/diab.44.7.790
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis in Obese African-Americans

Abstract: Our preliminary data indicate that 15% of African-American patients presenting with diabetic ketoacidosis (DKA) are obese. To determine underlying mechanisms, we analyzed the clinical characteristics and indexes of insulin secretion and insulin sensitivity in 35 obese patients with DKA, 22 obese patients with hyperglycemia, 10 lean patients with DKA, and 10 obese nondiabetic subjects. Studies were performed 1 day after resolution of DKA and after 12 weeks of follow-up. At presentation, both obese DKA and obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
182
6
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(210 citation statements)
references
References 0 publications
15
182
6
7
Order By: Relevance
“…This association was evidenced, with a predominance of insulin secretory defect in metabolic studies of atypical diabetes [1,2,9]. Predominant insulin secretory defect is known to be a feature of Type II diabetes in populations of African ancestry [14,15].…”
Section: For Debatementioning
confidence: 99%
See 2 more Smart Citations
“…This association was evidenced, with a predominance of insulin secretory defect in metabolic studies of atypical diabetes [1,2,9]. Predominant insulin secretory defect is known to be a feature of Type II diabetes in populations of African ancestry [14,15].…”
Section: For Debatementioning
confidence: 99%
“…Latent autoimmune diabetes is not plausible since late appearance of islet-cell autoimmunity has not been reported. Obesity, which is an exceptional finding in classic Type I diabetes, is found in up to 56 % of the cohorts of patients with this atypical presentation [8] and mean BMI varies between 26 and 37 kg/m 2 [1,2,9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although DKA in patients with T2DM tends to have less severe acidosis (18,19), our patient had severe acidosis. Our patient also had a high insulin requirement, which may not be unusual for DKA in T2DM, as patients may require larger amounts of insulin to correct hyperglycemia (20).…”
Section: Discussionmentioning
confidence: 99%
“…On a more positive note, other studies have shown that about 50 to 66% of patients with T2DM who were admitted to the hospital due to DKA and required insulin on discharge, were able to stop insulin at some point (4,20,22). This may reflect recovery of beta cell function after resolution of the acute hyperglycemic episode (glucotoxicity).…”
Section: Discussionmentioning
confidence: 99%